Expression of ABCG2 Associated with Tumor Response in Metastatic Colorectal Cancer Patients Receiving First-line FOLFOX Therapy – Preliminary Evidence. Issue 2 (April 2013) - Lin, Pei-Ching; Lin, Hung-Hsin; Lin, Jen-Kou; Lin, Chun-Chi; Yang, Shung-Haur; Li, Anna Fen-Yau; Chen, Wei-Shone; Chang, Shih-Ching
Purpose: We retrospectively analyzed ABCG2 expression levels in patients with metastatic colorectal cancer (CRC) to investigate the interaction between ABCG2 expression and the tumor response to oxaliplatin and 5-fluorouracil (FOLFOX). Methods: Forty-three patients with CRC with liver metastasis who received first-line FOLFOX treatment at our institution between 2008 and 2010 were enrolled. ABCG2 expression was assessed by immunohistochemistry. Tumor response was determined using the modified Response Evaluation Criteria in Solid Tumors criteria. Results: At least 50% tumor shrinkage was observed in 16/43 patients (37.2%), including a complete response in 1 patient. According to the intensity of ABCG2 expression and the percentage of tumor cells expressing ABCG2, 21 tumors displayed high ABCG2 expression. Among these tumors, only 2 (9.5%) exhibited partial responses to FOLFOX; conversely, 63.6% of tumors with low ABCG2 expression (14/22) responded to FOLFOX. Primary and corresponding metastatic samples were available for 15 patients, and 13 of the metastatic tumors had higher ABCG2 expression than the corresponding primary tumors, but only 1 of these tumors responded to FOLFOX (7.7%). Conclusions: ABCG2 expression is associated with the tumor response to FOLFOX in patients with metastatic CRC. ABCG2 may be a selective marker for the efficacy of FOLFOX in treating CRC.